Analisis Proses Manufaktur Alat Pengepres Geram Mesin Perkakas - Muas M; Arthur Halik R; Dian Ekawati; Ahmad Hasbullah; Satria Anggara Samudra (Jurnal Teknik Mesin Sinergi, 2019)
Scattred industrial trash on mechanical company’s workshop will be dangerous for operator and employee. The aims of this research are to design, analyze and compare the function of automatic press tool of machining trash to a manual process. Method of this research are designing, manufacturing and testing. A tool was designed using inventor software, assembled and manufactured, then tested. As results, trash becomes neater, smaller, thus easier moved to the recycle process. It can operate with 2 ton maximum pressure and dimention 28,6 cm x 28,6 cm with 25 cm depth. Press tool  produces an average pressing time with an automatic system 21.89 sec and reduction in space volume 7.670,7 mm3,whereas manual process, average pressing time 34,38 sec, space volume reduction 5.887,3 mm3.